Enhanced skeletal muscle contractile function and corticospinal excitability precede strength and architectural adaptations during lower-limb resistance training - Wilson, M. T.; Hunter, A. M.; Fairweather, M.; Kerr, S.; Hamilton, F. L.; Macgregor, L. J. (European Journal of Applied Physiology, 2023)
Purpose Evolving investigative techniques are providing greater understanding about the early neuromuscular responses to resistance training among novice exercisers. The aim of this study was to investigate the time-course of changes in muscle contractile mechanics, architecture, neuromuscular, and strength adaptation during the first 6-weeks of lower-limb resistance training.